Fragmentation and integration: new evidence on the organisational structure of UK firms - Riegler, Robert (2012)
This thesis will discuss how fragmented UK firms are and how they have changed between 1997 - 2008. We examine possible explanations for fragmentation and try to capture the effects of fragmentation on employment and labour productivity. We consider an organisational and a spatial dimension of fragmentation for the manufacturing and the tradable service sector. The data used comes from the Business Structure Database - a firm and plant level database which captures 99 percent of UK economic activity.